Aluminum-silicon-magnesium alloy material for anti-corrosion aluminum doors and windows and preparation process thereof

CN122979715APending Publication Date: 2026-10-27TANGSHAN KUNDA TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611450550.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-18
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0006]针对现有技术的不足,本发明提供了一种抗腐蚀铝门窗用铝硅镁系合金材料及其制备工艺,解决了现有的铝门窗用铝合金材料在复杂服役环境中易发生晶间腐蚀、点蚀以及电偶腐蚀,且在提升耐腐蚀性能时往往伴随合金拉伸强度和塑性下降的问题

Benefits of technology

[0048]1、本发明通过控制合金中锶、钛、碳及杂质硼等元素的含量,改变了合金内部富铁相的结晶形态并细化了铸态晶粒,降低了杂质相与铝基体之间的电势差,同时避免了第二相粒子在材料内部的偏析与团聚,减少了点蚀和电偶腐蚀的引发源,提高了合金材料的抗局部腐蚀能力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application relates to the field of aluminum alloy materials, and discloses an aluminum-silicon-magnesium alloy material for anti-corrosion aluminum doors and windows and a preparation process thereof, which comprises silicon, magnesium, iron, strontium, chromium, titanium, carbon, aluminum and inevitable impurities, and the contents of the impurities and boron elements are limited. The preparation process is as follows: melting the raw materials and adding a refining agent to remove gas; adding aluminum-strontium intermediate alloy, filtering, adding aluminum-titanium-carbon intermediate alloy, and preparing round ingots through semi-continuous direct water-cooling casting; sequentially carrying out two-stage temperature rising homogenization treatment, hot extrusion forming, two-stage online water-cooling quenching, temperature uniform treatment, stretching and double-stage artificial aging treatment. The alloy elements are controlled to cooperate with the deformation heat treatment steps, the as-cast grains are refined, the impurity phase crystallization form is changed, the strengthening phase is uniformly precipitated in the material, and the local enrichment of the solute elements is reduced. The material maintains a high tensile strength, reduces the internal potential difference, and improves the intergranular corrosion resistance and the pitting corrosion resistance of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of aluminum alloy materials, specifically to an aluminum-silicon-magnesium alloy material for corrosion-resistant aluminum doors and windows and its preparation process. Background Technology

[0002] Aluminum-silicon-magnesium alloys are widely used in the manufacturing of building doors and windows due to their good mechanical properties and processing capabilities. However, in complex outdoor service environments, existing aluminum alloy materials for doors and windows are prone to localized corrosion and intergranular corrosion, and existing manufacturing methods cannot simultaneously achieve both high strength and high corrosion resistance of the alloy.

[0003] In the prior art, iron impurities inside the alloy tend to form an iron-rich phase during solidification, and the potential difference between the phase and the aluminum matrix can easily cause pitting corrosion and galvanic corrosion. At the same time, conventional grain refinement methods can easily lead to the segregation and agglomeration of second-phase particles inside the material, further increasing the induction source of localized corrosion.

[0004] In the deformation and heat treatment stages, conventional processes often fail to balance the mechanical properties and corrosion resistance of materials. To improve the tensile strength of alloys, conventional heat treatment and deformation processes often lead to temperature differences and uneven stress within the material, and promote the concentration and enrichment of solute elements at grain boundaries. This state undermines the corrosion resistance of grain boundaries, providing a continuous path for intergranular corrosion, resulting in a significant decrease in elongation after fracture and resistance to intergranular corrosion while achieving higher strength.

[0005] Furthermore, during the alloy smelting stage, molten aluminum readily absorbs hydrogen and incorporates oxide films and non-metallic inclusions. Conventional refining methods have limited ability to dissolve the oxide film on the melt surface and to adsorb and separate fine inclusions within the melt, making it difficult to completely remove gases and suspended matter from the melt. These residual gas cavities and non-metallic impurities not only reduce the structural density of the finished material during subsequent processing and service, but also directly evolve into potential sources of corrosion initiation. Summary of the Invention

[0006] To address the shortcomings of existing technologies, this invention provides an aluminum-silicon-magnesium alloy material for corrosion-resistant aluminum doors and windows and its preparation process. This solves the problem that existing aluminum alloy materials for aluminum doors and windows are prone to intergranular corrosion, pitting corrosion, and galvanic corrosion in complex service environments, and that improving corrosion resistance is often accompanied by a decrease in the alloy's tensile strength and plasticity.

[0007] To achieve the above objectives, the present invention provides the following technical solution:

[0008] In a first aspect, the present invention provides an aluminum-silicon-magnesium alloy material for corrosion-resistant aluminum doors and windows, employing the following technical solution:

[0009] A corrosion-resistant aluminum-silicon-magnesium alloy material for aluminum doors and windows, comprising the following components by mass fraction:

[0010] Silicon: 0.42%–0.49%;

[0011] Magnesium: 0.55%–0.65%;

[0012] Iron: 0.10%–0.12%;

[0013] Strontium: 0.015%~0.022%;

[0014] Chromium: 0.06%–0.085%;

[0015] Titanium: 0.006%~0.012%;

[0016] Carbon: 0.0003%~0.0006%;

[0017] The remaining components are aluminum and unavoidable impurities, and the sum of the mass fractions of all components is 100%.

[0018] Of the unavoidable impurities, the mass fraction of a single impurity element does not exceed 0.01%, and the total mass fraction of the impurity elements does not exceed 0.05%; the mass fraction of boron does not exceed 0.0010%.

[0019] The corrosion-resistant aluminum-silicon-magnesium alloy material for aluminum doors and windows is obtained by melting and casting the components to obtain aluminum alloy round ingots. The aluminum alloy round ingots are subjected to homogenization treatment including two-stage heating, then hot extrusion molding to obtain extruded profiles, followed by online water cooling quenching. The residual heat after the online water cooling quenching is used to raise and stabilize the surface temperature of the extruded profiles at 60℃~90℃ before stretching. Finally, it is obtained by two-stage artificial aging treatment. The final heating temperature of the first stage of the two-stage heating is 350℃~380℃, and the final heating temperature of the second stage is 530℃~540℃. The first holding temperature of the two-stage artificial aging is 105℃~115℃, and the second holding temperature is 175℃~185℃.

[0020] By adopting the above technical solution, this invention improves the internal microstructure of the alloy material and reduces its tendency for localized corrosion by controlling the specific content of alloying elements and combining them with heat treatment processes, thus obtaining an aluminum alloy material with good strength, plasticity, and corrosion resistance. The specific working process is as follows:

[0021] The first step involves iron forming a rich iron phase during aluminum alloy solidification. The potential difference between this phase and the aluminum matrix easily triggers galvanic corrosion and pitting. The addition of strontium alters the growth pattern of the rich iron phase, changing its morphology from elongated needle-like to granular. Simultaneously, strontium dissolves in the aluminum matrix, reducing the potential difference between the rich iron phase and the aluminum matrix, thus decreasing the alloy's tendency for localized breakdown and galvanic corrosion.

[0022] The second step involves using titanium and carbon to generate a titanium carbide phase within the alloy, which acts as a grain refiner to refine the as-cast grains. Simultaneously, the boron mass fraction is limited to no more than 0.0010%. This limitation is achieved by using an aluminum-titanium-carbon master alloy as a grain refiner to introduce titanium and carbon during the smelting process, replacing conventional boron-containing aluminum-titanium-boron master alloys. Furthermore, no other boron-containing raw materials or auxiliary reagents are intentionally added during the entire batching and smelting process, effectively controlling the introduction of boron. This method avoids the segregation and agglomeration of the boron-containing second phase within the material, reducing pitting corrosion initiation sources.

[0023] In the third step, chromium precipitates as a chromium-containing phase during homogenization. Two-stage heating causes the low-melting-point phase to dissolve while retaining the chromium-containing phase. During subsequent hot deformation processing, the chromium-containing phase inhibits the complete recrystallization of the alloy, resulting in an interlaced distribution of internal microstructure boundaries. This disrupts the straightness and continuity of corrosion channels, thereby inhibiting the propagation of intergranular corrosion into the alloy material.

[0024] The fourth step involves online water-cooling quenching followed by homogenization and stretching, which increases the degree of deformation within the alloy and provides conditions for the subsequent precipitation of strengthening phases. In the two-stage artificial aging treatment, the first stage of low-temperature aging promotes the aggregation of solute elements; the second stage of high-temperature aging promotes the precipitation and growth of strengthening phases within the grains. This staged treatment method avoids excessive enrichment of solute elements in local areas, prevents the formation of continuous precipitation bands, and while improving the yield strength of the material, reduces the potential difference in local areas, thereby improving the mechanical properties and resistance to intergranular corrosion of the alloy material.

[0025] Secondly, the present invention provides a preparation process for corrosion-resistant aluminum-silicon-magnesium alloy materials for aluminum doors and windows, employing the following technical solution:

[0026] A preparation process for an aluminum-silicon-magnesium alloy material for corrosion-resistant aluminum doors and windows includes the following steps:

[0027] Industrial pure aluminum ingots are melted to obtain molten aluminum. Crystalline silicon, aluminum-iron master alloy, aluminum-chromium master alloy and pure magnesium ingot are added to obtain an alloy melt. An auxiliary refining agent is added for refining, and argon gas is introduced for degassing to obtain a refined alloy melt.

[0028] An aluminum-strontium master alloy is added to the refined alloy melt to obtain a modified alloy melt. The modified alloy melt is then filtered to obtain a filtered alloy melt. Subsequently, an aluminum-titanium-carbon master alloy is added to the filtered alloy melt to obtain a final alloy melt, which is then semi-continuously and directly water-cooled to produce an aluminum alloy round ingot, which is then cooled to room temperature.

[0029] The aluminum alloy round ingot is heated and held at a certain temperature in two stages to homogenize the temperature. After the heating and holding process is completed, it is cooled to room temperature.

[0030] The homogenized aluminum alloy round ingot is heated and held at a certain temperature, then hot-extruded to obtain an extruded profile, which is then subjected to online water-cooled quenching.

[0031] The residual heat after online water-cooling quenching is used to perform a uniform temperature treatment on the extruded profile, so that the surface temperature of the extruded profile rises and stabilizes at 60℃~90℃. Then, it is stretched to obtain a stretched profile. The stretched profile is naturally cooled to room temperature and placed at room temperature. After that, the stretched profile is subjected to a two-stage artificial aging treatment. After being taken out of the furnace and air-cooled to room temperature, the finished product of aluminum-silicon-magnesium alloy material for corrosion-resistant aluminum doors and windows is obtained.

[0032] By adopting the above technical solution, this invention achieves uniform internal composition distribution of the alloy through controlling the order of alloy element addition and the deformation heat treatment process. The multi-stage heat treatment process after semi-continuous casting regulates the heating and cooling rates and deformation timing, allowing the strengthening phase to precipitate uniformly in the matrix. This improves the material strength while reducing the local enrichment of solute elements, resulting in a finished alloy material with high strength and corrosion resistance.

[0033] Preferably, the auxiliary refining agent is made from raw materials comprising the following parts by weight: 40 to 50 parts by weight of sodium chloride powder, 40 to 50 parts by weight of potassium chloride powder, and 5 to 10 parts by weight of sodium fluoroaluminate powder.

[0034] The preparation method of the auxiliary refining agent includes: placing sodium chloride powder, potassium chloride powder and sodium fluoroaluminate powder in a mixer and stirring and mixing at room temperature for 30 min to obtain a mixed powder; placing the mixed powder in a drying oven and drying at 120℃ for 2 h to obtain a dried mixed powder; cooling to room temperature and sealing for storage.

[0035] The amount of auxiliary refining agent used accounts for 0.085% to 0.110% of the total theoretical alloy feed. The total theoretical alloy feed is the total mass of industrial pure aluminum ingots, crystalline silicon, aluminum-iron master alloy, aluminum-chromium master alloy, pure magnesium ingots, aluminum-strontium master alloy, and aluminum-titanium-carbon master alloy added.

[0036] The process of adding crystalline silicon, aluminum-iron master alloy, aluminum-chromium master alloy and pure magnesium ingot to obtain alloy melt is as follows: crystalline silicon, aluminum-iron master alloy and aluminum-chromium master alloy are added in sequence, followed by pure magnesium ingot and stirring to obtain alloy melt; when adding crystalline silicon, aluminum-iron master alloy and aluminum-chromium master alloy, the temperature of aluminum liquid is controlled at 725℃~740℃, and when adding pure magnesium ingot, the temperature of aluminum liquid is controlled at 710℃~725℃.

[0037] The flow rate of argon gas introduced during the degassing process is 12L / min to 18L / min. The degassing process is carried out using a rotary jet degassing device with a rotor speed of 350r / min to 450r / min and a degassing time of 8min to 12min. After the degassing process, the slag on the surface of the alloy melt is removed.

[0038] By employing the above technical solution, the auxiliary refining agent melts on the surface of the melt, and sodium fluoroaluminate dissolves the alumina film on the surface of the melt. The molten salt layer formed by sodium chloride and potassium chloride isolates oxygen from the air and adsorbs inclusions separated from the molten aluminum. Argon gas is introduced during the degassing process, dispersing into bubbles within the molten pool. The partial pressure difference between the inside and outside of these bubbles adsorbs and carries dissolved hydrogen from the molten aluminum to the surface of the melt. This purification process eliminates pitting corrosion initiation sources caused by gases and non-metallic inclusions within the alloy material. The addition of pure magnesium ingots after cooling reduces the oxidation loss of magnesium, ensuring the accuracy of the alloy composition ratio.

[0039] Preferably, the process of adding aluminum-strontium master alloy to the refined alloy melt is as follows: the temperature of the refined alloy melt is controlled at 700℃~715℃, the aluminum-strontium master alloy is added, stirred and allowed to stand, and the total processing time from the time all the aluminum-strontium master alloy is added is set to 10min~20min to obtain the modified alloy melt; the modified alloy melt is filtered using a ceramic foam filter plate, and the filtration is performed after the ceramic foam filter plate is preheated; the process of adding aluminum-titanium-carbon master alloy to the filtered alloy melt is as follows: the filtered alloy melt is introduced into the flow channel, and the aluminum-titanium-carbon master alloy is added to the filtered alloy melt in the flow channel; the semi-continuous direct water-cooled casting is performed by conveying the final alloy melt to the crystallizer for semi-continuous direct water-cooled casting, the casting speed of the semi-continuous direct water-cooled casting is controlled at 110mm / min~130mm / min, and the cooling water temperature is controlled at 22℃~28℃.

[0040] By employing the above technical solutions, controlling the addition temperature and settling time of the aluminum-strontium master alloy allows strontium to diffuse within the melt, altering the crystallization conditions of the iron-rich phase and reducing the tendency for galvanic corrosion. Adding the aluminum-titanium-carbon master alloy during the laminator stage shortens the residence time of the titanium-carbon phase in the high-temperature melt, preventing precipitation and agglomeration, promoting rapid melt crystallization, and increasing ingot density. Preheated ceramic foam filters intercept suspended solids remaining from the initial slagging reaction.

[0041] Preferably, in the two-stage heating homogenization process, the first stage starts from room temperature and heats to 350℃~380℃ at an average furnace temperature rise rate of 40℃ / h~60℃ / h. The second stage heats to 530℃~540℃ at an average furnace temperature rise rate of 15℃ / h~20℃ / h and holds the temperature. The holding time in the homogenization process is 6h~8h. After heating and holding in the homogenization process, the cooling process to room temperature is as follows: first, forced air cooling is performed to reduce the core temperature of the aluminum alloy round ingot to 300℃. The average cooling rate of the forced air cooling is controlled at 300℃ / h~480℃ / h, and then it is naturally cooled to room temperature.

[0042] By adopting the above technical solution, the first stage of heating eliminates the internal stress generated during the ingot crystallization process; the second stage of slow heating allows the low-melting-point phase to dissolve steadily into the aluminum matrix, avoiding local overheating caused by rapid heating. After homogenization and heat preservation, forced air cooling is performed, which allows the matrix to quickly cross the precipitation temperature range of the strengthening phase, inhibiting the concentrated precipitation of the strengthening phase in local areas, retaining alloying elements in the matrix, and reducing the local potential difference inside the material.

[0043] Preferably, hot extrusion forming is carried out in a preheated extrusion die; during hot extrusion forming, the heating temperature of the aluminum alloy round ingot is 475℃~490℃, the preheating temperature of the extrusion die is 450℃~480℃, and the exit temperature of the extruded profile is 510℃~530℃; online water cooling quenching is divided into two stages. The first stage starts when the surface temperature of the extruded profile drops to 500℃. During the process of the surface temperature of the extruded profile dropping from 500℃ to 250℃, the average cooling rate is 15℃ / s~25℃ / s; the second stage cools the surface temperature of the extruded profile from 250℃ to 40℃~60℃, with an average cooling rate of 5℃ / s~12℃ / s. Online water cooling quenching is stopped when the surface temperature of the extruded profile reaches 40℃~60℃.

[0044] By adopting the above technical solution, the extrusion temperature parameters ensure that the material maintains the solid solution state of the elements during hot deformation. In online water-cooling quenching, the first stage of rapid water cooling retains the solute elements in the matrix; the second stage reduces the cooling rate and controls the termination temperature range, reducing the thermal stress between the profile surface and core, avoiding deformation and warping, while the appropriate amount of residual heat retained provides conditions for subsequent cross-sectional isostatic treatment.

[0045] Preferably, the temperature equalization treatment involves turning on the circulating airflow to raise and stabilize the surface temperature of the extruded profile at 60℃~90℃; controlling the time interval from stopping online water-cooling quenching to starting stretching to 300s; during stretching, the extruded profile produces a permanent elongation of 0.8%~1.5%; the stretching time is controlled at 5s~30s; the two-stage artificial aging treatment involves placing the stretched profile in an air-circulating aging furnace. In the first stage, the stretched profile is heated to 105℃~115℃ and held for 2.5h~3.5h; in the second stage, no cooling is performed, and the air-circulating aging furnace is controlled to continue heating to 175℃~185℃ within 30min~75min and held for 4h~5h.

[0046] By adopting the above technical solutions, the cross-sectional isothermal treatment eliminates the temperature difference of the cross-section after quenching, ensuring that the profile maintains a consistent deformation state. The tensile operation increases the degree of deformation within the material, providing a basis for the subsequent precipitation of strengthening phases. In the two-stage artificial aging treatment, the first stage of low-temperature aging promotes the directional aggregation of solute elements; the second stage of high-temperature aging promotes the precipitation of strengthening phases. The combined steps of deformation and heat treatment reduce the concentrated enrichment of solute elements in localized areas, lowering the potential difference within the material. This allows the alloy material to maintain high tensile strength while exhibiting good resistance to intergranular corrosion and pitting corrosion.

[0047] This invention provides an aluminum-silicon-magnesium alloy material for corrosion-resistant aluminum doors and windows, and its preparation process. It has the following beneficial effects:

[0048] 1. This invention changes the crystallization morphology of the iron-rich phase inside the alloy and refines the cast grains by controlling the content of elements such as strontium, titanium, carbon and impurity boron in the alloy. This reduces the potential difference between the impurity phase and the aluminum matrix, while avoiding the segregation and agglomeration of second phase particles inside the material, reducing the initiation source of pitting corrosion and galvanic corrosion, and improving the resistance of the alloy material to localized corrosion.

[0049] 2. This invention employs a deformation heat treatment process that includes two-stage heating, homogenization, isothermal treatment, stretching, and two-stage artificial aging. This process regulates the precipitation of strengthening phases within the alloy, eliminates internal temperature differences, and provides a deformation basis for the precipitation of strengthening phases. The staged aging treatment avoids the concentrated accumulation of solute elements at grain boundaries, disrupting the continuous channels of intergranular corrosion. This allows the alloy to maintain high tensile strength and elongation after fracture while improving its resistance to intergranular corrosion.

[0050] 3. This invention purifies the alloy melt by using an auxiliary refining agent prepared from a mixture of sodium chloride, potassium chloride, and sodium fluoroaluminate, combined with argon degassing and filtration processes. The refining agent forms a coating layer on the melt surface, dissolving the oxide film and adsorbing inclusions. Argon gas removes hydrogen from the molten aluminum, and filtration removes residual suspended matter. The melt purification process reduces gas shrinkage cavities and non-metallic inclusions within the material, eliminates potential corrosion initiation sources, and ensures the structural density of the finished alloy material. Detailed Implementation

[0051] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the preparation examples, examples, comparative examples, and test examples. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0052] The sources and specifications of the main raw materials and reagents used in the following examples and comparative examples are as follows. Reagents not specifically mentioned are all commercially available analytical grade or higher products. The industrial pure aluminum ingots, crystalline silicon, pure magnesium ingots, sodium chloride, potassium chloride, sodium fluoroaluminate, and the following aluminum-based master alloys used in this experiment are all commercially available conventional metallurgical or chemical raw materials.

[0053] The mass fraction of Al (aluminum) in industrial pure aluminum ingots is not less than 99.85%, of which the background mass fraction of Fe (iron) is less than 0.06% and the background mass fraction of Si (silicon) is less than 0.04%.

[0054] The mass fraction of Si in crystalline silicon is not less than 99.0%.

[0055] The mass fraction of Mg in pure magnesium ingots is not less than 99.9%.

[0056] The purity of sodium chloride, potassium chloride, and sodium fluoroaluminate is not less than 99.0%, and the particle size is 40-100 mesh.

[0057] The argon gas used in the experiment was high-purity argon gas with a purity of not less than 99.999%.

[0058] The mass fraction of Fe in the aluminum-iron master alloy is 20%, with the balance being Al and unavoidable impurities.

[0059] The mass fraction of Cr (chromium) in the aluminum-chromium master alloy is 5%, with the balance being Al and unavoidable impurities.

[0060] The Sr (strontium) mass fraction in the aluminum-strontium master alloy is 10%, with the balance being Al and unavoidable impurities.

[0061] The aluminum-titanium-carbon master alloy contains 3% Ti (titanium) by mass, 0.15% C (carbon) by mass, and the balance is Al and unavoidable impurities.

[0062] The aluminum-titanium-boron master alloy contains 5% Ti by mass, 1% B by mass, and the balance is Al and unavoidable impurities.

[0063] The method of limiting the boron content in alloy materials according to the present invention is as follows: during the smelting process, the above-mentioned aluminum-titanium-carbon master alloy is selected as a grain refiner to introduce titanium and carbon elements, replacing the conventional aluminum-titanium-boron master alloy containing boron. Furthermore, no other raw materials or auxiliary reagents containing boron are intentionally added during the entire batching and smelting process, thereby effectively controlling the introduction of boron and ensuring that the mass fraction of boron in the final corrosion-resistant aluminum-silicon-magnesium alloy material for aluminum doors and windows does not exceed 0.0010%.

[0064] Preparation Example 1:

[0065] This preparation example provides an auxiliary refining agent, the preparation method of which includes the following steps:

[0066] (1) Place 40g sodium chloride powder, 40g potassium chloride powder and 5g sodium fluoroaluminate powder in a mixer and stir and mix at room temperature for 30 minutes to obtain mixed powder.

[0067] (2) Place the mixed powder in a drying oven and dry it at 120°C for 2 hours to obtain dried mixed powder; cool the dried mixed powder to room temperature and then seal it for storage.

[0068] Preparation Example 2:

[0069] This preparation example provides an auxiliary refining agent, the preparation method of which includes the following steps:

[0070] (1) Place 45g sodium chloride powder, 45g potassium chloride powder and 7.5g sodium fluoroaluminate powder in a mixer and stir and mix at room temperature for 30 minutes to obtain mixed powder.

[0071] (2) Place the mixed powder in a drying oven and dry it at 120°C for 2 hours to obtain dried mixed powder; cool the dried mixed powder to room temperature and then seal it for storage.

[0072] Preparation Example 3:

[0073] This preparation example provides an auxiliary refining agent, the preparation method of which includes the following steps:

[0074] (1) Place 50g sodium chloride powder, 50g potassium chloride powder and 10g sodium fluoroaluminate powder in a mixer and stir and mix at room temperature for 30 minutes to obtain mixed powder.

[0075] (2) Place the mixed powder in a drying oven and dry it at 120°C for 2 hours to obtain dried mixed powder; cool the dried mixed powder to room temperature and then seal it for storage.

[0076] Example 1:

[0077] This embodiment provides a preparation process for an aluminum-silicon-magnesium alloy material for corrosion-resistant aluminum doors and windows, including the following steps:

[0078] (1) Alloy smelting and refining.

[0079] In this embodiment, a theoretical alloy feed total of 100,000 kg is considered as one furnace batch. Based on mass fraction and without considering element burn-off, the theoretical feed amounts of each raw material in this embodiment are: 96.980 kg of industrial pure aluminum ingots, 0.420 kg of crystalline silicon, 0.550 kg of pure magnesium ingots, 0.500 kg of aluminum-iron master alloy, 1.200 kg of aluminum-chromium master alloy, 0.150 kg of aluminum-strontium master alloy, and 0.200 kg of aluminum-titanium-carbon master alloy. During actual feeding, the weighing values ​​of each raw material are corrected based on the measured composition of the industrial pure aluminum ingots, crystalline silicon, pure magnesium ingots, and each aluminum-based master alloy, as well as the predetermined element yield.

[0080] The alloy material was prepared by mixing raw materials according to the formula proportions, and samples were taken and tested at the beginning and middle stages of casting to confirm that the resulting alloy material met the following chemical composition: the sum of the mass fractions of each element was 100%, of which silicon (Si) was 0.42%, magnesium (Mg) was 0.55%, iron (Fe) was 0.10%, strontium (Sr) was 0.015%, chromium (Cr) was 0.06%, titanium (Ti) was 0.006%, carbon (C) was 0.0003%, and the balance was aluminum (Al) and unavoidable impurities; the mass fraction of a single unavoidable impurity element did not exceed 0.01%, and the total mass fraction of unavoidable impurity elements did not exceed 0.05%; no raw materials or auxiliary reagents containing boron (B) were intentionally added during the entire batching and smelting process, and the mass fraction of boron (B) was controlled to not exceed 0.0010%.

[0081] Industrial pure aluminum ingots were added to an aluminum alloy melting furnace and melted at 720°C. After the industrial pure aluminum ingots were completely melted and molten aluminum was obtained, the temperature was further increased to control the temperature of the molten aluminum at 725°C. Crystalline silicon, aluminum-iron master alloy, and aluminum-chromium master alloy were added sequentially, and the mixture was stirred and held at this temperature for 15 minutes. Subsequently, the temperature of the molten aluminum was lowered to 710°C, pure magnesium ingots were added, and the mixture was stirred for 2 minutes to completely melt the pure magnesium ingots, thus obtaining an alloy melt.

[0082] The alloy melt temperature was maintained at 710℃. All 85g of auxiliary refining agent prepared in Preparation Example 1 was evenly sprinkled onto the surface of the alloy melt. The amount of auxiliary refining agent was 0.085% of the theoretical total alloy feed. A rotary jet degassing device was used, with argon gas as the degassing medium. The argon gas flow rate was controlled at 12L / min, the degassing rotor speed at 350r / min, and the distance between the lower end of the rotor and the bottom of the molten pool at 150mm. The degassing time was 8min. After degassing, the slag on the surface of the alloy melt was removed to obtain the refined alloy melt.

[0083] (2) Deterioration, filtration and casting.

[0084] The temperature of the refined alloy melt was controlled at 700℃. 0.150 kg of aluminum-strontium master alloy was added to the refined alloy melt, and the time when all the aluminum-strontium master alloy was added was taken as the starting point. The mixture was stirred at a speed of 60 r / min for 2 minutes, and then allowed to stand until the total processing time from the time when all the aluminum-strontium master alloy was added reached 10 minutes, thus obtaining the modified alloy melt. The modified alloy melt was then filtered through a 30 ppi (pores per inch) ceramic foam filter plate preheated at 400℃ for 30 minutes to obtain the filtered alloy melt.

[0085] The filtered alloy melt was introduced into a casting bath, and 0.200 kg of aluminum-titanium-carbon master alloy was added to it. The amount of aluminum-titanium-carbon master alloy added was 0.20% of the theoretical total alloy feed, resulting in the final alloy melt. The final alloy melt was then conveyed through the casting bath to a semi-continuous direct water-cooled casting crystallizer, with the conveying time from the casting bath to the crystallizer controlled at 2 minutes. The melt temperature at the crystallizer entrance was controlled at 690℃, the casting speed at 130 mm / min, the cooling water temperature at 22℃, and the cooling water flow rate at 35 L / min for semi-continuous direct water-cooled casting, producing aluminum alloy round ingots with a diameter of 120 mm. The aluminum alloy round ingots were then cooled to room temperature.

[0086] (3) Homogenization treatment.

[0087] The cylindrical aluminum alloy round ingots cooled to room temperature are loaded into a homogenization furnace and heated from room temperature to the first stage heating final temperature of 350°C at an average furnace temperature rise rate of 40°C / h. Then the average furnace temperature rise rate is adjusted to 15°C / h, and the temperature is continued to rise to the second stage heating final temperature of 530°C and held for 6 hours.

[0088] After the heat preservation process, the aluminum alloy round ingot is transferred to the forced air cooling station. A sheathed thermocouple is inserted into the aluminum alloy round ingot through a blind hole pre-set on it, with the thermocouple's measuring end positioned at the geometric center of the ingot to monitor the core temperature. The cooling airflow is adjusted based on the core temperature measurement. During the process of reducing the core temperature of the aluminum alloy round ingot from 530℃ to 300℃, the average cooling rate of the forced air cooling is controlled at 300℃ / h. When the core temperature of the aluminum alloy round ingot reaches 300℃, the forced air cooling is stopped, allowing the ingot to cool naturally to room temperature.

[0089] (4) Hot extrusion and online quenching.

[0090] The homogenized aluminum alloy round ingot is heated to 475℃, and then held at that temperature for 30 minutes after the core temperature reaches 475℃. The extrusion die is preheated to 450℃, and the held aluminum alloy round ingot is fed into the extrusion press and hot-extruded through the preheated extrusion die to obtain an extruded profile. The exit temperature of the extruded profile is controlled at 510℃.

[0091] After the extruded profile leaves the extrusion die, it undergoes online water quenching within 2 seconds. The online water quenching first reduces the surface temperature of the extruded profile to 500℃, with this point as the starting point. During the reduction of the surface temperature from 500℃ to 250℃, the average cooling rate is 15℃ / s. When the surface temperature reaches 250℃, the cooling water flow rate is adjusted to achieve an average cooling rate of 5℃ / s from 250℃ to 40℃. Online water quenching is immediately stopped when the surface temperature reaches 40℃.

[0092] (5) Stretch straightening and artificial aging.

[0093] After stopping the online water-cooling quenching, the extruded profile is transferred to a cooling bed homogenization zone equipped with a semi-enclosed adjustable baffle curtain. The residual heat from the online water-cooling quenching is used to homogenize the extruded profile; that is, the circulating airflow is activated to allow the surface temperature of the extruded profile to rise and stabilize at 60℃. The time interval from stopping the online water-cooling quenching to starting the stretching is controlled at 300s. A stretching straightener is used to stretch the extruded profile, achieving a permanent elongation of 0.8%, with the stretching time controlled at 5s to obtain the stretched profile. The stretched profile is then allowed to cool naturally to room temperature and left at room temperature for 0.5 hours, followed by a two-stage artificial aging treatment.

[0094] The stretched profiles were placed in an air-circulating aging furnace and heated to the first-stage holding temperature of 105℃ for 2.5 hours. After the holding period, without cooling, the air-circulating aging furnace was continuously heated to the second-stage holding temperature of 175℃ within 30 minutes and held for 4 hours. After artificial aging, the profiles were removed from the furnace and air-cooled to room temperature to obtain the finished aluminum-silicon-magnesium alloy material for corrosion-resistant aluminum doors and windows.

[0095] Example 2:

[0096] This embodiment provides a preparation process for an aluminum-silicon-magnesium alloy material for corrosion-resistant aluminum doors and windows, including the following steps:

[0097] (1) Alloy smelting and refining.

[0098] In this embodiment, a theoretical alloy feed total of 100,000 kg is considered as one furnace batch. Based on mass fraction and without considering element burn-off, the theoretical feed amounts of each raw material in this embodiment are: 96.460 kg of industrial pure aluminum ingots, 0.455 kg of crystalline silicon, 0.600 kg of pure magnesium ingots, 0.550 kg of aluminum-iron master alloy, 1.450 kg of aluminum-chromium master alloy, 0.185 kg of aluminum-strontium master alloy, and 0.300 kg of aluminum-titanium-carbon master alloy. During actual feeding, the weighing values ​​of each raw material are corrected based on the measured composition of the industrial pure aluminum ingots, crystalline silicon, pure magnesium ingots, and each aluminum-based master alloy, as well as the predetermined element yield.

[0099] The alloy material was prepared by mixing raw materials according to the formula proportions, and samples were taken and tested at the beginning and middle stages of casting to confirm that the resulting alloy material met the following chemical composition: the sum of the mass fractions of each element was 100%, of which Si was 0.455%, Mg was 0.60%, Fe was 0.11%, Sr was 0.0185%, Cr was 0.0725%, Ti was 0.009%, C was 0.00045%, and the balance was Al and unavoidable impurities; the mass fraction of a single unavoidable impurity element did not exceed 0.01%, and the total mass fraction of unavoidable impurity elements did not exceed 0.05%; no raw materials or auxiliary reagents containing element B were intentionally added during the entire batching and smelting process, and the mass fraction of element B was controlled to not exceed 0.0010%.

[0100] Industrial pure aluminum ingots were added to an aluminum alloy melting furnace and melted at 730°C. After the industrial pure aluminum ingots were completely melted and molten aluminum was obtained, the temperature was further increased to control the temperature of the molten aluminum at 732°C. Crystalline silicon, aluminum-iron master alloy, and aluminum-chromium master alloy were added sequentially, and the mixture was stirred and held at this temperature for 20 minutes. Subsequently, the temperature of the molten aluminum was lowered to 718°C, pure magnesium ingots were added, and the mixture was stirred for 3 minutes to completely melt the pure magnesium ingots, thus obtaining an alloy melt.

[0101] The alloy melt temperature was maintained at 718℃. All 97.5g of the auxiliary refining agent prepared in Preparation Example 2 was evenly sprinkled onto the surface of the alloy melt. The amount of auxiliary refining agent was 0.0975% of the theoretical total alloy feed. A rotary jet degassing device was used, with argon gas as the degassing medium. The argon gas flow rate was controlled at 15L / min, the degassing rotor speed at 400r / min, the distance between the lower end of the rotor and the bottom of the molten pool at 150mm, and the degassing time at 10min. After degassing, the slag on the surface of the alloy melt was removed to obtain the refined alloy melt.

[0102] (2) Deterioration, filtration and casting.

[0103] The temperature of the refined alloy melt was controlled at 708℃. 0.185 kg of aluminum-strontium master alloy was added to the refined alloy melt, and the timer was set from the moment when all the aluminum-strontium master alloy was added. The melt was stirred at 60 r / min for 3 min, and then allowed to stand until the total processing time from the moment all the aluminum-strontium master alloy was added reached 15 min, thus obtaining the modified alloy melt. The modified alloy melt was then filtered through a 40 ppi ceramic foam filter plate preheated at 420℃ for 30 min to obtain the filtered alloy melt.

[0104] The filtered alloy melt was introduced into a casting bath, and 0.300 kg of aluminum-titanium-carbon master alloy was added to it. The amount of aluminum-titanium-carbon master alloy added was 0.30% of the theoretical total alloy feed, resulting in the final alloy melt. The final alloy melt was then conveyed through the casting bath to a semi-continuous direct water-cooled casting crystallizer, with the conveying time from the casting bath to the crystallizer controlled at 3.5 min. The melt temperature at the crystallizer entrance was controlled at 698℃, the casting speed at 120 mm / min, the cooling water temperature at 25℃, and the cooling water flow rate at 40 L / min for semi-continuous direct water-cooled casting, producing aluminum alloy round ingots with a diameter of 150 mm. The aluminum alloy round ingots were then cooled to room temperature.

[0105] (3) Homogenization treatment.

[0106] The cylindrical aluminum alloy round ingots cooled to room temperature are loaded into a homogenization furnace and heated from room temperature to the first stage heating final temperature of 365°C at an average furnace temperature rise rate of 50°C / h. Then the average furnace temperature rise rate is adjusted to 17.5°C / h, and the temperature is continued to rise to the second stage heating final temperature of 535°C and held for 7 hours.

[0107] After the heat preservation process, the aluminum alloy round ingot is transferred to the forced air cooling station. A sheathed thermocouple is inserted into the aluminum alloy round ingot through a blind hole pre-set on it, with the thermocouple's measuring end positioned at the geometric center of the ingot to monitor the core temperature. The cooling airflow is adjusted based on the core temperature measurement. During the process of reducing the core temperature of the aluminum alloy round ingot from 535℃ to 300℃, the average cooling rate of the forced air cooling is controlled at 390℃ / h. When the core temperature reaches 300℃, the forced air cooling is stopped, allowing the aluminum alloy round ingot to cool naturally to room temperature.

[0108] (4) Hot extrusion and online quenching.

[0109] The homogenized aluminum alloy round ingot is heated to 482℃, and then held at that temperature for 45 minutes after the core temperature reaches 482℃. The extrusion die is preheated to 465℃, and the held aluminum alloy round ingot is fed into the extrusion press and hot-extruded through the preheated extrusion die to obtain an extruded profile. The exit temperature of the extruded profile is controlled at 520℃.

[0110] After the extruded profile leaves the extrusion die, it undergoes online water quenching within 2 seconds. The online water quenching first reduces the surface temperature of the extruded profile to 500℃, with this point as the starting point. During the process of reducing the surface temperature from 500℃ to 250℃, the average cooling rate is 20℃ / s. When the surface temperature reaches 250℃, the cooling water flow rate is adjusted to achieve an average cooling rate of 8.5℃ / s from 250℃ to 50℃. The online water quenching is immediately stopped when the surface temperature reaches 50℃.

[0111] (5) Stretch straightening and artificial aging.

[0112] After stopping the online water-cooling quenching, the extruded profiles are transferred to a cooling bed homogenization zone equipped with a semi-enclosed adjustable baffle curtain. The residual heat from the online water-cooling quenching is used to homogenize the extruded profiles; this is achieved by turning on the circulating airflow to raise and stabilize the surface temperature of the extruded profiles at 75°C. The time interval from stopping the online water-cooling quenching to starting the stretching is controlled at 300 seconds. A stretching straightener is used to stretch the extruded profiles to achieve a permanent elongation of 1.15%, and the stretching time is controlled at 17 seconds to obtain the stretched profiles. The stretched profiles are then allowed to cool naturally to room temperature and left at room temperature for 2 hours, followed by a two-stage artificial aging treatment.

[0113] The stretched profiles were placed in an air-circulating aging furnace and heated to the first-stage holding temperature of 110℃ for 3 hours. After the holding period, without cooling, the air-circulating aging furnace was continuously heated to the second-stage holding temperature of 180℃ within 52 minutes and held for 4.5 hours. After artificial aging, the profiles were removed from the furnace and air-cooled to room temperature to obtain the finished aluminum-silicon-magnesium alloy material for corrosion-resistant aluminum doors and windows.

[0114] Example 3:

[0115] This embodiment provides a preparation process for an aluminum-silicon-magnesium alloy material for corrosion-resistant aluminum doors and windows, including the following steps:

[0116] (1) Alloy smelting and refining.

[0117] In this embodiment, a theoretical alloy feed total of 100,000 kg is considered as one furnace batch. Based on mass fraction and without considering element loss during theoretical calculations, the theoretical feed amounts of each raw material in this embodiment are: 95.940 kg of industrial pure aluminum ingots, 0.490 kg of crystalline silicon, 0.650 kg of pure magnesium ingots, 0.600 kg of aluminum-iron master alloy, 1.700 kg of aluminum-chromium master alloy, 0.220 kg of aluminum-strontium master alloy, and 0.400 kg of aluminum-titanium-carbon master alloy. During actual feeding, the weighing values ​​of each raw material are corrected based on the measured composition of the industrial pure aluminum ingots, crystalline silicon, pure magnesium ingots, and each aluminum-based master alloy, as well as the predetermined element yield.

[0118] The alloy material was prepared by mixing raw materials according to the formula proportions, and samples were taken and tested at the beginning and middle stages of casting to confirm that the resulting alloy material met the following chemical composition: the sum of the mass fractions of each element was 100%, of which Si was 0.49%, Mg was 0.65%, Fe was 0.12%, Sr was 0.022%, Cr was 0.085%, Ti was 0.012%, C was 0.0006%, and the balance was Al and unavoidable impurities; the mass fraction of a single unavoidable impurity element did not exceed 0.01%, and the total mass fraction of unavoidable impurity elements did not exceed 0.05%; no raw materials or auxiliary reagents containing element B were intentionally added during the entire batching and smelting process, and the mass fraction of element B was controlled to not exceed 0.0010%.

[0119] Industrial pure aluminum ingots were added to an aluminum alloy melting furnace and melted at 740°C. After the industrial pure aluminum ingots were completely melted and molten aluminum was obtained, the temperature was maintained at 740°C. Crystalline silicon, aluminum-iron master alloy, and aluminum-chromium master alloy were added sequentially, stirred, and held at this temperature for 25 minutes. Subsequently, the temperature of the molten aluminum was lowered to 725°C, pure magnesium ingots were added, and stirred for 5 minutes to completely melt the pure magnesium ingots, obtaining an alloy melt.

[0120] The alloy melt temperature was maintained at 725℃. All 110g of auxiliary refining agent prepared in Preparation Example 3 was evenly sprinkled onto the surface of the alloy melt. The amount of auxiliary refining agent was 0.110% of the theoretical total alloy feed. A rotary jet degassing device was used, with argon gas as the degassing medium. The argon gas flow rate was controlled at 18L / min, the degassing rotor speed at 450r / min, the distance between the lower end of the rotor and the bottom of the molten pool at 150mm, and the degassing time at 12min. After degassing, the slag on the surface of the alloy melt was removed to obtain the refined alloy melt.

[0121] (2) Deterioration, filtration and casting.

[0122] The temperature of the refined alloy melt was controlled at 715℃. 0.220 kg of aluminum-strontium master alloy was added to the refined alloy melt, and the timer was set from the moment when all the aluminum-strontium master alloy was added. The melt was stirred at 60 r / min for 4 min, and then allowed to stand until the total processing time from the moment all the aluminum-strontium master alloy was added reached 20 min, thus obtaining the modified alloy melt. The modified alloy melt was then filtered through a 50 ppi ceramic foam filter plate preheated at 450℃ for 30 min to obtain the filtered alloy melt.

[0123] The filtered alloy melt was introduced into a casting bath, and 0.400 kg of aluminum-titanium-carbon master alloy was added to it. The amount of aluminum-titanium-carbon master alloy added was 0.40% of the theoretical total alloy feed, resulting in the final alloy melt. The final alloy melt was then conveyed through the casting bath to a semi-continuous direct water-cooled casting crystallizer, with the conveying time from the casting bath to the crystallizer controlled at 5 min. The melt temperature at the crystallizer entrance was controlled at 705℃, the casting speed at 110 mm / min, the cooling water temperature at 28℃, and the cooling water flow rate at 45 L / min for semi-continuous direct water-cooled casting, producing an aluminum alloy round ingot with a diameter of 180 mm. The aluminum alloy round ingot was then cooled to room temperature.

[0124] (3) Homogenization treatment.

[0125] The cylindrical aluminum alloy round ingots cooled to room temperature are loaded into a homogenization furnace and heated from room temperature to the first stage heating final temperature of 380°C at an average furnace temperature rise rate of 60°C / h. Then the average furnace temperature rise rate is adjusted to 20°C / h, and the temperature is continued to rise to the second stage heating final temperature of 540°C and held for 8 hours.

[0126] After the heat preservation process, the aluminum alloy round ingot is transferred to the forced air cooling station. A sheathed thermocouple is inserted into the aluminum alloy round ingot through a blind hole pre-set on it, with the thermocouple's measuring end positioned at the geometric center of the ingot to monitor the core temperature. The cooling airflow is adjusted based on the core temperature measurement. During the process of reducing the core temperature of the aluminum alloy round ingot from 540℃ to 300℃, the average cooling rate of the forced air cooling is controlled at 480℃ / h. When the core temperature reaches 300℃, the forced air cooling is stopped, allowing the aluminum alloy round ingot to cool naturally to room temperature.

[0127] (4) Hot extrusion and online quenching.

[0128] The homogenized aluminum alloy round ingot is heated to 490℃, and then held at that temperature for 60 minutes after the core temperature reaches 490℃. The extrusion die is preheated to 480℃, and the held aluminum alloy round ingot is fed into the extrusion press and hot-extruded through the preheated extrusion die to obtain an extruded profile. The exit temperature of the extruded profile is controlled at 530℃.

[0129] After the extruded profile leaves the extrusion die, it undergoes online water quenching within 2 seconds. The online water quenching first reduces the surface temperature of the extruded profile to 500℃, with this point as the starting point. During the process of reducing the surface temperature from 500℃ to 250℃, the average cooling rate is 25℃ / s. When the surface temperature reaches 250℃, the cooling water flow rate is adjusted to achieve an average cooling rate of 12℃ / s from 250℃ to 60℃. Online water quenching is immediately stopped when the surface temperature reaches 60℃.

[0130] (5) Stretch straightening and artificial aging.

[0131] After stopping the online water-cooling quenching, the extruded profile is transferred to a cooling bed homogenization zone equipped with a semi-enclosed adjustable baffle curtain. The residual heat from the online water-cooling quenching is used to homogenize the extruded profile; that is, the circulating airflow is activated to allow the surface temperature of the extruded profile to rise and stabilize at 90℃. The time interval from stopping the online water-cooling quenching to starting the stretching is controlled at 300 seconds. A stretching straightener is used to stretch the extruded profile, achieving a permanent elongation of 1.5%, with the stretching time controlled at 30 seconds to obtain the stretched profile. The stretched profile is then allowed to cool naturally to room temperature and left at room temperature for 4 hours, followed by a two-stage artificial aging treatment.

[0132] The stretched profiles were placed in an air-circulating aging furnace and heated to the first-stage holding temperature of 115℃ for 3.5 hours. After the holding period, without cooling, the air-circulating aging furnace was continuously heated to the second-stage holding temperature of 185℃ within 75 minutes and held for 5 hours. After artificial aging, the profiles were removed from the furnace and air-cooled to room temperature to obtain the finished aluminum-silicon-magnesium alloy material for corrosion-resistant aluminum doors and windows.

[0133] Comparative Example 1:

[0134] Compared with Example 2, the difference in this comparative example is that: in step (2), 0.185 kg of aluminum-strontium master alloy is not added, and 0.185 kg of industrial pure aluminum ingot is used to supplement the theoretical alloy feed to 100.000 kg; at the same time, the stirring, settling and waiting operations related to the addition of aluminum-strontium master alloy are eliminated. In the obtained alloy, Sr is only a residual content introduced by the raw materials, and its measured mass fraction is less than 0.0001%. Except for the above differences, the other steps and parameters are the same as in Example 2.

[0135] Comparative Example 2:

[0136] Compared with Example 2, the difference in this comparative example is that in step (2), instead of adding 0.300 kg of aluminum-titanium-carbon master alloy, 0.180 kg of aluminum-titanium-boron master alloy and 0.120 kg of industrial pure aluminum ingot are added, so that the total mass of the added substances is still 0.300 kg. The theoretical Ti mass fraction introduced by the aluminum-titanium-boron master alloy is 0.009%, the theoretical B mass fraction is 0.0018%, and C element is not intentionally added. Except for the above differences, the other steps and parameters are the same as in Example 2.

[0137] Comparative Example 3:

[0138] Compared with Example 2, the difference in this comparative example is that in step (3), after the aluminum alloy round ingot is loaded into the homogenization furnace, it is directly heated from room temperature to 535°C at an average furnace temperature rise rate of 50°C / h and held at that temperature for 7 hours, thus eliminating the second-stage slow heating process at an average furnace temperature rise rate of 17.5°C / h. Apart from the above differences, the remaining steps and parameters are the same as in Example 2.

[0139] Comparative Example 4:

[0140] Compared with Example 2, the difference in this comparative example is that in step (5), after the extruded profile stops online water quenching and is transferred to the cooling bed, the circulating airflow is not turned on, the surface temperature of the profile is not raised and stabilized at 75°C, and the time interval between stopping online water quenching and starting stretching is not 300s. Instead, the extruded profile is allowed to cool naturally to 25°C before stretching begins. The actual time from stopping online water quenching to starting stretching is 45 minutes. The permanent elongation and subsequent artificial aging parameters of the extruded profile are the same as in Example 2. Except for the above differences, the other steps and parameters are the same as in Example 2.

[0141] Comparative Example 5:

[0142] Compared with Example 2, the difference in this comparative example is that in step (5), the stretched profile is naturally cooled to room temperature and placed at room temperature for 2 hours, then placed in an air-circulating aging furnace, directly heated to 180°C and held for 4.5 hours, eliminating the low-temperature aging stage of holding at 110°C for 3 hours. Apart from the above differences, the remaining steps and parameters are the same as in Example 2.

[0143] Comparative Example 6:

[0144] Compared with Example 2, the difference in this comparative example is as follows: In step (4), when the surface temperature of the extruded profile reaches 250°C, online water quenching is continued to cool the extruded profile to 25°C, and the average cooling rate in the temperature range of 250°C to 25°C is 8.0°C / s; In step (5), the profile cross-section isostatic operation in the cooling bed is cancelled, and stretching begins 120s after the online water quenching ends, with the profile cross-section temperature at the start of stretching being 25°C. Except for the differences in the cooling regime, isostatic operation, and stretching temperature, the other steps and parameters are the same as in Example 2.

[0145] Test Example 1:

[0146] This test example is used to determine the electrical conductivity of the alloy materials obtained in Examples 1-3, and specifically includes the following steps:

[0147] (1) Samples were cut from the finished aluminum-silicon-magnesium alloy materials for corrosion-resistant aluminum doors and windows prepared in Examples 1, 2 and 3 respectively, and processed into block samples with a length of 50 mm.

[0148] (2) The measuring surfaces of each sample were mechanically polished with silicon carbide water sandpaper of different grit sizes in turn to remove the oxide layer and processing marks on the measuring surfaces; then the measuring surfaces were mechanically polished, ultrasonically cleaned with anhydrous ethanol and dried to obtain a smooth measuring surface.

[0149] (3) Under an environment of 20℃±2℃, the eddy current conductivity meter was used with model SMP350 and probe operating frequency of 60kHz, in accordance with GB / T 12966-2022. The thickness of the sample measurement area was 10mm. Before measurement, the eddy current conductivity meter was calibrated using conductivity standard blocks with nominal conductivity of 29.33%IACS (international annealing copper standard) and 59.88%IACS, respectively.

[0150] (4) Place the probe of the eddy current conductivity meter vertically against the polished measurement surface of the sample. For each sample, randomly select 5 different locations on the measurement surface for measurement, record the conductivity measurement values ​​at each location, and calculate the arithmetic mean of the 5 measurement values. The conductivity measurement results are expressed as %IACS.

[0151] The test results are shown in Table 1.

[0152] Table 1. Conductivity test results of the alloy materials obtained in Examples 1 to 3:

[0153]

[0154] Test conclusion:

[0155] As shown in Table 1, the average electrical conductivity of the alloy materials prepared in Examples 1, 2 and 3 are 52.82% IACS, 54.17% IACS and 55.44% IACS, respectively.

[0156] The electrical conductivity of aluminum alloys is related to the content of solute atoms in the solid solution state within the aluminum matrix. When solute atoms precipitate from a supersaturated solid solution, the scattering effect of solute atoms on electron motion weakens, and the electrical conductivity of the material increases accordingly. The conductivity results shown in Table 1 indicate that the heat treatment processes used in Examples 1-3 are beneficial for promoting the precipitation of solute atoms from the supersaturated solid solution and reducing the content of solute atoms in the solid solution state within the aluminum matrix.

[0157] Test Example 2:

[0158] This test example is used to determine the room temperature tensile mechanical properties of the alloy materials prepared in Examples 1-3, Comparative Examples 4 and 6, and specifically includes the following steps:

[0159] (1) Tensile test blanks were cut from the finished aluminum-silicon-magnesium alloy materials for corrosion-resistant aluminum doors and windows prepared in Examples 1, 2, 3, 4 and 6, respectively, along the extrusion direction. The solid thickness of the sampled part of the extruded profile was not less than 12 mm, and a circular tensile test specimen with a diameter of 10 mm could be processed along the extrusion direction.

[0160] (2) The blank of the tensile specimen is machined with reference to GB / T 16865-2023 to prepare a room-temperature tensile specimen. The original gauge length of the room-temperature tensile specimen is 50 mm, and the diameter of the parallel portion is 10 mm.

[0161] (3) In an environment of 25°C, the tensile specimen is mounted between the upper chuck and the lower chuck of a universal material testing machine, and the position of the tensile specimen is adjusted to keep the tensile specimen vertical and clamped tightly; then an extensometer is mounted on the gauge length section of the tensile specimen.

[0162] (4) The universal material testing machine is started, and an axial tensile load is applied to the tensile specimen at a crosshead displacement rate of 2 mm / min until the tensile specimen fractures. The load and extensometer strain data are recorded by the software matched with the universal material testing machine, and the tensile strength and the specified non-proportional extension strength Rp0.2 (i.e., the stress corresponding to a non-proportional extension rate of 0.2% of the specimen, which is equivalent to the yield strength in engineering tests) are directly determined according to the load and extensometer strain data. After the tensile specimen fractures, the two fractured sections of the specimen are butted together, the post-fracture gauge length is measured, and the post-fracture elongation is calculated. Three parallel specimens are set for each group, the arithmetic mean of the test results of the three parallel specimens is taken as the test result of the group, and the standard deviation is calculated.

[0163] The test results are shown in Table 2.

[0164] Table 2. Test results of room-temperature tensile mechanical properties of the finished alloy materials prepared in Examples and Comparative Examples:

[0165]

[0166] Test conclusion:

[0167] It can be seen from Table 2 that the finished alloy materials prepared in Examples 1 to 3 have high tensile strength and yield strength, with a post-fracture elongation of 10.4% to 12.8%, indicating that the finished alloy materials prepared in Examples 1 to 3 still maintain a certain plasticity while obtaining high strength. Among them, the finished alloy material prepared in Example 2 has an average tensile strength of 261.2 MPa, an average yield strength of 239.5 MPa, and an average post-fracture elongation of 11.7%.

[0168] Comparing Example 2 with Comparative Examples 4 and 6, it can be seen that in Example 2, after the surface temperature of the profile reached 75°C, tensile strength and yield strength were 261.2 MPa and 239.5 MPa, respectively. In Comparative Example 4, the isothermal cooling process was omitted, and the profile was allowed to cool naturally to 25°C. Tensile strength was then performed 45 minutes after the online water quenching was stopped. The average tensile strength and yield strength were 243.6 MPa and 212.4 MPa, respectively. In Comparative Example 6, the profile was continuously water-quenched to 25°C, the isothermal cooling process was omitted, and tensile strength was performed at 25°C 120 seconds after the online water quenching ended. The average tensile strength and yield strength were 239.1 MPa and 207.2 MPa, respectively.

[0169] The above results indicate that, under the same alloy composition and artificial aging conditions, the cooling regime before stretching, the section isotherm operation, and the profile temperature at the start of stretching affect the mechanical properties of the final alloy material. The cooling, isotherm, and stretching processes used in Example 2 facilitate the coordination of the stretching deformation state with the subsequent artificial aging process, thereby improving the tensile strength and the specified non-proportional elongation strength Rp0.2 of the finished alloy material.

[0170] Test Example 3:

[0171] This test example is used to evaluate the intergranular corrosion resistance of the alloy materials prepared in Example 2, Comparative Example 3, and Comparative Example 5, and specifically includes the following steps:

[0172] (1) Block samples with a size of 40mm×30mm were cut from the finished aluminum-silicon-magnesium alloy materials for corrosion-resistant aluminum doors and windows prepared in Example 2, Comparative Example 3 and Comparative Example 5 respectively.

[0173] (2) Insulate and seal the non-exposed surfaces of each sample, leaving a 40mm×30mm surface as the corrosion exposure surface. Use silicon carbide sandpaper to mechanically polish the corrosion exposure surface, then use anhydrous ethanol for ultrasonic cleaning and dry with cold air to obtain the test sample.

[0174] (3) Preparation of intergranular corrosion test solution. The intergranular corrosion test solution is an aqueous solution of sodium chloride and hydrogen peroxide, wherein the mass concentration of sodium chloride is 57 g / L, and the amount of 30% hydrogen peroxide solution added is 10 mL / L. The temperature of the intergranular corrosion test solution is maintained at 30℃±1℃, and the ratio of the volume of the intergranular corrosion test solution to the corrosion exposure area of ​​the sample is 20 mL / cm². 2 .

[0175] (4) Immerse the sample to be tested completely in the intergranular corrosion test solution for 6 hours. After immersion, remove the sample, rinse the surface of the sample with distilled water to remove any residual solution, and dry it in the air.

[0176] (5) The dried sample was cut along a direction perpendicular to the exposed corrosion surface, and then the cut section was inlaid, ground and polished. The polished cut section was observed under an optical microscope, and the maximum corrosion depth extending from the exposed corrosion surface into the sample matrix was determined using measurement software. Three parallel samples were set up for each group, and the arithmetic mean of the maximum corrosion depth of the three parallel samples was taken as the average maximum corrosion depth of the group.

[0177] The test results are shown in Table 3.

[0178] Table 3. Test results of intergranular corrosion depth of alloy materials prepared in Example 2 and the comparative example:

[0179]

[0180] Test conclusion:

[0181] As shown in Table 3, the average maximum corrosion depth of the alloy material obtained in Example 2 after intergranular corrosion testing was 54.4 μm. The average maximum corrosion depths of the alloy materials obtained in Comparative Examples 3 and 5 were 123.1 μm and 151.8 μm, respectively, both greater than those in Example 2, indicating that the alloy material obtained in Example 2 has better resistance to intergranular corrosion.

[0182] The difference between Example 2 and Comparative Example 3 lies in the heating regime for homogenization treatment. Comparative Example 3 directly heated the aluminum alloy round ingot from room temperature to 535°C at an average furnace temperature rise rate of 50°C / h and held it at that temperature for 7 hours. This eliminated the slow heating process in Example 2, where the furnace temperature rose from 365°C to 535°C at an average rise rate of 17.5°C / h, thus shortening the time the ingot spent in the 365–535°C temperature range. Test results show that the slow heating process affects the microstructure and intergranular corrosion susceptibility of the finished alloy material.

[0183] The difference between Example 2 and Comparative Example 5 lies in the artificial aging process. Comparative Example 5 omits the low-temperature aging stage of holding at 110°C for 3 hours and directly raises the temperature to 180°C and holds for 4.5 hours. Its average maximum corrosion depth increases to 151.8 μm, indicating that the alloy material obtained after omitting the low-temperature aging stage has increased intergranular corrosion sensitivity and increased extent of intergranular corrosion propagation into the matrix.

[0184] Example 2 employed a homogenization process including slow heating and a two-stage artificial aging process, resulting in a significantly smaller average maximum corrosion depth compared to Comparative Examples 3 and 5. These results demonstrate that the combined effect of homogenization and two-stage artificial aging processes can inhibit the propagation of intergranular corrosion into the alloy matrix, thereby improving the intergranular corrosion resistance of aluminum alloy profiles used in doors and windows.

[0185] Test Example 4:

[0186] This test example is used to evaluate the electrochemical corrosion resistance of the alloy materials prepared in Example 2, Comparative Example 1, and Comparative Example 2, and specifically includes the following steps:

[0187] (1) Block samples were cut from the finished alloy materials prepared in Example 2, Comparative Example 1 and Comparative Example 2 respectively.

[0188] (2) Insulate and seal the non-exposed surfaces of each sample, leaving an area of ​​1 cm². 2 The surface of the electrode is used as the exposed surface of the working electrode. The exposed surface of the working electrode is mechanically polished with silicon carbide wet sandpaper, then washed with water and dried with cold air to obtain the working electrode.

[0189] (3) Prepare a 3.5% sodium chloride aqueous solution as the electrolyte. The test was conducted using an electrochemical workstation at 25°C. A three-electrode system was used, with the working electrode being the aforementioned alloy sample, the reference electrode being a saturated calomel electrode, and the counter electrode being a platinum sheet.

[0190] (4) Immerse the working electrode in the electrolyte and maintain it in an open-circuit state for at least 30 minutes, until the open-circuit potential fluctuates by no more than 2 mV over 5 minutes. Then perform a potentiodynamic polarization scan, starting from a point 250 mV negative relative to the open-circuit potential, ending at 0 mV (vs. SCE, i.e., relative to a saturated calomel electrode). The scan direction is from negative to positive potential, and the scan rate is 1 mV / s. The anolyte current density in the polarization curve should reach 10 μA / cm². 2 The potential corresponding to the continuous rise in voltage is determined as the breakdown potential.

[0191] (5) Conduct galvanic current testing. Connect the alloy sample with a 304 stainless steel sample having the same exposed area via galvanic connection, and immerse them in the above-mentioned 3.5% sodium chloride aqueous solution, ensuring a distance of 5 mm between the exposed surfaces of the two samples. Continue testing for 12 hours, recording the galvanic current density using a zero-resistance galvanometer. The arithmetic mean of the absolute values ​​of the galvanic current density within the last 30 minutes before the end of the test is taken as the galvanic current density of the parallel sample. Set up 3 parallel samples for each group, and use the arithmetic mean of the test results of the 3 parallel samples as the test result of the group, calculating the standard deviation.

[0192] The test results are shown in Table 4.

[0193] Table 4. Electrochemical corrosion resistance test results of the alloy materials prepared in Example 2 and the comparative example:

[0194]

[0195] Test conclusion:

[0196] As shown in Table 4, the average breakdown potential of the alloy material obtained in Example 2 is -682.0 mV (vs. SCE), and the average galvanic current density is 4.35 μA / cm². 2 The alloy material obtained in Comparative Example 1 had an average breakdown potential of -747.7 mV (vs. SCE) and an average galvanic current density of 15.62 μA / cm². 2 The alloy material obtained in Comparative Example 2 had an average breakdown potential of -738.3 mV (vs. SCE) and an average galvanic current density of 13.88 μA / cm². 2 .

[0197] The average breakdown potential of Example 2 was higher than that of Comparative Example 1, and the average galvanic current density was lower than that of Comparative Example 1, indicating that the Sr modification treatment used in Example 2 was beneficial to reducing the local breakdown tendency and galvanic corrosion tendency of the alloy material in sodium chloride aqueous solution.

[0198] Example 2 employed an Al-Ti-C grain refinement system. Comparative Example 2 used 0.180 kg of aluminum-titanium-boron master alloy and 0.120 kg of industrially pure aluminum ingot to replace the 0.300 kg of aluminum-titanium-carbon master alloy in Example 2, maintaining the theoretical Ti mass fraction at 0.009% and the theoretical B mass fraction at 0.0018%, without intentionally adding C. The average breakdown potential of Example 2 was higher than that of Comparative Example 2, and the average galvanic current density was lower, indicating that under the test conditions, the alloy material corresponding to the Al-Ti-C grain refinement system and B content control method used in Example 2 has a lower tendency for localized breakdown and galvanic corrosion.

[0199] In summary, the alloy material obtained in Example 2 exhibits a high breakdown potential and a low galvanic current density in a 3.5% sodium chloride aqueous solution, indicating that the alloy composition and preparation process used in Example 2 are beneficial to improving the pitting corrosion resistance and galvanic corrosion resistance of the alloy material.

[0200] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, adjustments, substitutions and modifications can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A corrosion-resistant aluminum-silicon-magnesium alloy material for aluminum doors and windows, characterized in that, Components containing the following mass fractions: Silicon: 0.42%–0.49%; Magnesium: 0.55%–0.65%; Iron: 0.10%–0.12%; Strontium: 0.015%~0.022%; Chromium: 0.06%–0.085%; Titanium: 0.006%~0.012%; Carbon: 0.0003%~0.0006%; The remaining components are aluminum and unavoidable impurities, and the sum of the mass fractions of all components is 100%. Of the unavoidable impurities, the mass fraction of a single impurity element does not exceed 0.01%, and the total mass fraction of the impurity elements does not exceed 0.05%; the mass fraction of boron does not exceed 0.0010%.

2. A preparation process for an aluminum-silicon-magnesium alloy material for corrosion-resistant aluminum doors and windows, characterized in that, The preparation of the corrosion-resistant aluminum-silicon-magnesium alloy material for aluminum doors and windows as described in claim 1 includes the following steps: Industrial pure aluminum ingots are melted to obtain molten aluminum. Crystalline silicon, aluminum-iron master alloy, aluminum-chromium master alloy and pure magnesium ingot are added to obtain an alloy melt. An auxiliary refining agent is added for refining, and argon gas is introduced for degassing to obtain a refined alloy melt. An aluminum-strontium master alloy is added to the refined alloy melt to obtain a modified alloy melt. The modified alloy melt is then filtered to obtain a filtered alloy melt. Subsequently, an aluminum-titanium-carbon master alloy is added to the filtered alloy melt to obtain a final alloy melt, which is then semi-continuously and directly water-cooled to produce an aluminum alloy round ingot, which is then cooled to room temperature. The aluminum alloy round ingot is heated and held at a certain temperature in two stages to homogenize the temperature. After the heating and holding process is completed, it is cooled to room temperature. The homogenized aluminum alloy round ingot is heated and held at a certain temperature, then hot-extruded to obtain an extruded profile, which is then subjected to online water-cooled quenching. The residual heat after online water-cooling quenching is used to perform a uniform temperature treatment on the extruded profile, so that the surface temperature of the extruded profile rises and stabilizes at 60℃~90℃. Then, it is stretched to obtain a stretched profile. The stretched profile is naturally cooled to room temperature and placed at room temperature. After that, the stretched profile is subjected to a two-stage artificial aging treatment. After being taken out of the furnace and air-cooled to room temperature, the finished product of aluminum-silicon-magnesium alloy material for corrosion-resistant aluminum doors and windows is obtained.

3. The preparation process according to claim 2, characterized in that, The auxiliary refining agent is made from raw materials comprising the following parts by weight: 40 to 50 parts by weight of sodium chloride powder, 40 to 50 parts by weight of potassium chloride powder, and 5 to 10 parts by weight of sodium fluoroaluminate powder. The preparation method of the auxiliary refining agent includes: The sodium chloride powder, potassium chloride powder, and sodium fluoroaluminate powder are placed in a mixer and stirred at room temperature for 30 minutes to obtain a mixed powder; the mixed powder is placed in a drying oven and dried at 120°C for 2 hours to obtain a dried mixed powder, which is then cooled to room temperature and sealed for storage. The amount of the auxiliary refining agent used accounts for 0.085% to 0.110% of the total theoretical alloy feed weight. The total theoretical alloy feed weight is the total mass of the industrial pure aluminum ingot, the crystalline silicon, the aluminum-iron master alloy, the aluminum-chromium master alloy, the pure magnesium ingot, the aluminum-strontium master alloy, and the aluminum-titanium-carbon master alloy added.

4. The preparation process according to claim 2, characterized in that, The process of adding crystalline silicon, aluminum-iron master alloy, aluminum-chromium master alloy, and pure magnesium ingot to obtain the alloy melt is as follows: The crystalline silicon, the aluminum-iron master alloy, and the aluminum-chromium master alloy are added sequentially, followed by the addition of pure magnesium ingots and stirring to obtain the alloy melt; When the crystalline silicon, the aluminum-iron master alloy and the aluminum-chromium master alloy are added, the temperature of the molten aluminum is controlled at 725℃~740℃; when the pure magnesium ingot is added, the temperature of the molten aluminum is controlled at 710℃~725℃. The argon gas flow rate introduced during the degassing process is 12L / min to 18L / min. The degassing process is carried out using a rotary jet degassing device with a degassing rotor speed of 350r / min to 450r / min and a degassing time of 8min to 12min. After the degassing process, the slag on the surface of the alloy melt is removed.

5. The preparation process according to claim 2, characterized in that, The process of adding the aluminum-strontium master alloy to the refined alloy melt is as follows: The temperature of the refined alloy melt is controlled at 700℃~715℃. After adding the aluminum-strontium master alloy, the mixture is stirred and allowed to stand. The total processing time from the time the aluminum-strontium master alloy is completely added is set to 10min~20min to obtain the modified alloy melt. The filtration is performed on the modified alloy melt using a ceramic foam filter plate, and is carried out after the ceramic foam filter plate is preheated. The process of adding the aluminum-titanium-carbon master alloy to the filter alloy melt is as follows: The filter alloy melt is introduced into a flow channel, and the aluminum-titanium-carbon master alloy is added to the filter alloy melt in the flow channel; The semi-continuous direct water-cooled casting involves transporting the final alloy melt to a crystallizer for semi-continuous direct water-cooled casting. The casting speed of the semi-continuous direct water-cooled casting is controlled at 110 mm / min to 130 mm / min, and the cooling water temperature is controlled at 22℃ to 28℃.

6. The preparation process according to claim 2, characterized in that, In the two-stage heating homogenization process, the first stage starts from room temperature and heats to 350℃~380℃ at an average furnace temperature rise rate of 40℃ / h~60℃ / h. The second stage heats to 530℃~540℃ at an average furnace temperature rise rate of 15℃ / h~20℃ / h and then holds the temperature. The holding time in the homogenization process is 6h~8h. The process of cooling to room temperature after heating and holding in the homogenization process is as follows: Forced air cooling is first performed to reduce the core temperature of the aluminum alloy round ingot to 300°C. The average cooling rate of the forced air cooling is controlled at 300°C / h to 480°C / h, and then it is naturally cooled to room temperature.

7. The preparation process according to claim 2, characterized in that, The hot extrusion molding is performed in a preheated extrusion die; During the hot extrusion forming process, the heating temperature of the aluminum alloy round ingot is 475℃~490℃, the preheating temperature of the extrusion die is 450℃~480℃, and the exit temperature of the extruded profile is 510℃~530℃.

8. The preparation process according to claim 2, characterized in that, The online water-cooled quenching is divided into two stages. The first stage starts when the surface temperature of the extruded profile drops to 500°C. During the process of the surface temperature of the extruded profile dropping from 500°C to 250°C, the average cooling rate is 15°C / s to 25°C / s. In the second stage, the surface temperature of the extruded profile is cooled from 250°C to 40°C to 60°C, with an average cooling rate of 5°C / s to 12°C / s. The online water quenching is stopped when the surface temperature of the extruded profile reaches 40°C to 60°C.

9. The preparation process according to claim 2, characterized in that, The temperature equalization process involves turning on the circulating airflow to raise and stabilize the surface temperature of the extruded profile at 60°C to 90°C. The time interval from stopping the online water-cooling quenching to starting the stretching is controlled to be 300s. During the stretching, the extruded profile produces a permanent elongation of 0.8% to 1.5%, and the stretching time is controlled to be between 5s and 30s.

10. The preparation process according to claim 2, characterized in that, The two-stage artificial aging treatment involves placing the stretched profile in an air-circulating aging furnace. In the first stage, the stretched profile is heated to 105℃~115℃ and then held at that temperature for 2.5h~3.5h. The second stage does not involve cooling; instead, the air-circulating aging furnace is controlled to continue heating to 175°C–185°C within 30–75 minutes and held at that temperature for 4–5 hours.